A study of possible biohazards in the fluorescent antibody test using adenovirus, coxsackievirus, herpesvirus, and respiratory syncytial virus as antigens. - Bardell, D (1976)
Infectious adenovirus type 5 and coxsackievirus type B5, both nonlipid-containing viruses, were isolated from cells fixed in acetone at 22 degrees C for 15 min, from acetone used for fixation, from the solution used for washing slides during the fluorescent antibody procedure, and after complete processing of antigen preparations with serial twofold dilutions of human antisera and fluorescein-labeled goat anti-human immunoglobulin G. Lipid-containing herpes simplex virus type 1 and respiratory syncytial virus were inactivated by acetone, and infectious virus could not be recovered at any stage in the fluorescent antibody test. Fixation in acetone at 56 degrees C destroyed the infectivity of adenovirus 5 and coxsackievirus B5 within 30 min, but no adverse effect on the antigenic determinants of either virus occurred until after 60 min, thus demonstrating that these antigens can be utilized without the hazard of infectious virus.